TUMPAH TINDIH DALAM PROSES PERIZINAN KLINIK PRATAMA DI DINAS PENANAMAN MODAL DAN PELAYANAN TERPADU SATU PINTU KOTA PADANG - Gusman, Delfina; WD, Marryo Borry (Universitas Ekasakti, 2018)
Clinics are health care facilities that provide individual health services that provide basic medical and / or specialist services. Primary Clinic is a clinic that provides basic medical services both general and special. To establish primary clinics until they can operate through a series of licensing processes, namely the Hinder Ordonnantie (HO) Permit, Clinical Establishment Permit (IMK) and Clinical Operational Permit (IOK). The results of the process are overlapping or suggesting requirements that make the process ineffective and inefficient